Impeller trimming of an Industrial Centrifugal Viscous Oil Pump - Wen Guang Li (International Journal of Advanced Design and Manufacturing Technology, 2011)
Abstract: Impeller trimming is a proper way to alter the performance of centrifugal pump with a constant speed so as to meet the demand on the specified flow rate and head in pumping systems. The affinity law accounting for the impeller trimming is the key relation to determine the pump performance with a trimmed impeller. There seems no experimental study dealing with such an affinity law for centrifugal oil pump handling water and viscous oils. In this paper, an experimental investigation into the performance of an industrial centrifugal oil pump of type 65Y60 was explored when the original impeller was trimmed four times. In the experiments water and viscous oils served as the working liquid, respectively. The trimming exponents at both best efficiency and shut-off points were worked out, and compared to those in the existing affinity law for impeller diameter reduction and water. These exponents are very helpful for engineers to determine a trimmed impeller diameter for centrifugal oil pumps handling water and viscose oils with a relative high viscosity. Meanwhile the “rising-efficiency effect” was revealed when a trimmed impeller is delivering highly viscous oils.